Frequent occurrence of tetrodotoxin in the marine gastropod \(Nassarius glans\) causing a food poisoning in Khanh Hoa province, Vietnam in 2020 - Ha, Dao Viet; Le Ho, Khanh Hy; Pham, Xuan Ky; Bui, Quang Nghi; Nguyen, Phuong Anh; Phan, Bao Vy; Doan, Thi Thiet (Vietnam Journal of Marine Science and Technology, 2023)
A fatal neurotoxic poisoning case happened in Khanh Hoa province in 2020 after eating a certain number of marine gastropods, later identified as Nassarius glans, one of the common marine gastropods in Vietnam. As the remaining causative food in the incident, 62 specimens were collected to examine tetrodotoxin toxicity individual variation and frequency of toxic specimens by using HILIC/MS-MS analysis. 100% of studied specimens exhibited toxicity (556 ± 821 MU/g) beyond the regulatory level of consumption (10 MU/g) for puffer(fish) recommended in Japan and extensive variation (18–4,046 MU/g). The result pointed out that only 5 g of soft tissue from N. glans (equivalent to 2–3 specimens) containing maximum toxicity detected in the present study may cause human death if consumed. Fhe first time, this study identified TTXs in the gastropods as a causative toxin in the poisoning in Vietnam. Moreover, 65.5% of studied specimens with high toxicity higher than 100 MU/g, including 16.1%, showing extremely high toxicity (> 1,000 MU/g). The results suggested that this gastropod is quite dangerous for human consumption and should be alerted to public awareness.